Morphological Variation of Cultivated and Wild Apis cerana Honeybee from the Highland and Lowland in Yogyakarta - Fajriningsih, Rizki; Suwartiningsih, Nurul (Proceeding International Conference on Religion, Science and Education, 2022)
Apis cerana honey bees in Yogyakarta have a high potential. There has been no research on the morphology of cultivated and wild Apis cerana honeybees from the highlands and lowlands in Yogyakarta. The purpose of this study was to compare the morphology of cultivated and wild Apis cerana honeybees from the highlands and lowlands in Yogyakarta. Cultivated and wild Apis cerana honeybees from the highlands and lowlands of Yogyakarta were taken by 20 individuals each as samples. Wild honeybees are taken using sweep net while cultivated honeybees are taken using plastic. Honey bees are further preserved and observed morphologically. The main characters observed as many as six characters and the total morphological characters were 51 characters. The main character is analyzed with an average different test and a BNT test, while the grouping uses 51 characters analyzed with dendrogram creation. The results showed that there was a significant difference in the character of proboscis length: front wing length of the cultivated Apis cerana honeybee from the highlands which show the highest value. Honeybees from lowlands both cultivated and wild have the highest similarity (dissimilarity value of 1,549) compared to honeybees from the highlands. Wild honeybees from lowlands and highlands also have high similarity (dissimilarity value 1,762). It can be concluded that proboscis length: front wing lenght is an important distinguishing character for determining the habitat of Apis cerana honeybees.